2021
DOI: 10.21009/jpeb.009.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Job Satisfaction and Its Implications for the Lecturers Performance

Abstract: The purpose of this research is to examine the positive effects of leadership style, work environment, and organizational climate on lecturer performance through Pamulang University’s job satisfaction. Researchers used the quantitative research method in this study. The data was collected by using questionnaires distributed through surveys. Proportional random sampling was used, earning 135 samples, and partial least squares (PLS) were used for statistical analysis. The results show that leadership style, work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…Another finding from Anwar,Chandrarin,Darsono,& Respati 18 shows that a transformative leader will encourage a better institution through knowledge transfer. Other studies also have found that job satisfaction can be explained through several things, one of which is the main one is leadership in the organization 19 .…”
Section: Resultsmentioning
confidence: 96%
“…Another finding from Anwar,Chandrarin,Darsono,& Respati 18 shows that a transformative leader will encourage a better institution through knowledge transfer. Other studies also have found that job satisfaction can be explained through several things, one of which is the main one is leadership in the organization 19 .…”
Section: Resultsmentioning
confidence: 96%
“…As per discussed in the past literature, the work-related aspects involving teaching and learning, supervision of the postgraduate students, publication in reputable indexed journals, securing research grant and consultation are the one which closely related to the individual performance target or KPIs (Khan & Anwar, 2021;Basarudin et al, 2016;Masron et al, 2012). While non-work related issues include performing administrative tasks, working environment or culture and fulfilling the additional requirement such as the completion of PGDHELT are discussed as challenges for the newly appointed academic staffs (Mgaiwa, 2021;Subarto et al, 2021;Han et al, 2020;Sabagh et al, 2018). The in-depth interview had been conducted has clarified that the newly appointed academic staffs struggled to clearly gauge their individual performance benchmarks or KPIs.…”
Section: Discussionmentioning
confidence: 99%
“…Problem Statement is the the appointment of the new academic staff in the university is significant to allow new fresh ideas while injecting positive working culture within the university's environment (Ali et al, 2020). However, these new staffs could face with various issues and challenges in carrying their role as a lecturer, thus affecting their performance (Subarto, Solihin & Qurbani, 2021;Flux, Hassett & Callanan, 2020). According to Subarto et al (2021), from the external perspective, the issues pertaining to the working environment, the faculty's leadership as well the organizational culture are among the challenges faced by the university's academic staffs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Job satisfaction theories include twofactor theory, theory of hierarchy of needs, existence, relatedness, growth theory, and learned needs theory (Valaei & Rezaei, 2016). The most researched area of organizational behavior is job satisfaction over the years (Ćulibrk et al, 2018;Jamal & Anwar, 2021;Loan, 2020;Scanlan & Still, 2019;Subarto et al, 2021). It's crucial to know how satisfied employees are at work for a variety of reasons, and the results of job satisfaction surveys have an impact on both employees and employers.…”
Section: Job Satisfactionmentioning
confidence: 99%